Sosialisasi dan Implementasi K3 Upaya Peningkatan Keselamatan Kerja di Alfamidi Cabang Pasuruan - Hafidz Putra Perdana; Mentari Clara Dewanti (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
PT MIDI Utama Indonesia Tbk continues to face challenges in the implementation of Occupational Health and Safety (OHS/K3), including suboptimal employee understanding, uneven compliance with the use of personal protective equipment, and incomplete workplace safety supervision. This community service activity aims to enhance awareness, compliance, and implementation of OHS as an effort to control workplace accident risks and improve operational efficiency. The method applied was an implementative approach through socialization of work risk identification, OHS training, and the direct application of safety standards. The activity was conducted in the office and warehouse areas of Alfamidi Branch 2 Pasuruan, involving office employees, warehouse employees divided into two sessions according to the shift system, suppliers, as well as store managers and regional coordinators who participated online. The implementation involved company management, human resource practitioners, security personnel, and relevant institutions. Prior to the activity, understanding and compliance with OHS procedures were not evenly distributed, and the application of safety standards was not consistently implemented. Following the activity, there was an increase in awareness and compliance among all participants regarding OHS principles, operational activities became more orderly, and the potential for disruptions and workplace accident risks decreased.